Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Dalam Memecahkan Masalah - Ika Bella (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This study aims to find out how the application of the problem-based learning model can improve students' critical thinking skills in solving problems in science material for fifth grade students at SD Negeri 83 Palembang. The population in this study were students of SD Negeri 83 Palembang with a sample of students from class V.A as an experimental class using the Problem Based Learning model and the control class using conventional learning models at SD Negeri 83 Palembang. The research method used in this study is quantitative research, the type of research used is Quasi Experiment Design, with the form of this research design being the Nonequivalent Control Group Design. The data analysis technique uses an independent sample t-test. Based on the data analysis, it can be concluded: significance value = 0.01 if compared to 0.05, then a significant value of 0.01 <0.05 in this case Ha is accepted and Ho is rejected, therefore the research hypothesis is that there is a difference in ability after being given treatment in the control class uses a conventional learning model and the experimental class uses the Problem Based Learning learning model. Calculations in this study used the SPSS 22 application. Keywords: Problem Based Learning Model; Critical Thinking.